Poetic Resistance: The Role of Samalanga Poetry in Dutch Colonial Discourse During the Aceh War - Fadhli (Center for Research and Development of Religious Literature and Heritage, 2025)
This article examines the role of literature in shaping narratives during the Aceh War against the Dutch. While Hikayat Prang Sabi served as a literary expression of Acehnese resistance, the Dutch employed Samalanga Poetry to boost the morale of their soldiers. Despite both sides utilizing literature as a tool in warfare, each literary work reflects distinct perspectives, ideological foundations, and cultural frameworks. This research shows that Aceh, which is known for its Islamic values that are deeply rooted in the social structure, includes religious values in their literary works. In contrast to the Dutch, soldiers who went into battle were promised worldly pleasures such as wealth, rank and position as a reward for winning the war. Even though they differ in orientation, both of them use religious leaders as the main actors and patrons in raising the enthusiasm of their fighters. Drawing upon C. Nieuwenhuis' travel notes and a range of historical documents, this research explores how a community’s worldview influences the literary forms it produces. The analysis reveals that literature does not merely document historical events but also serves as a reflection of broader societal values, shaping collective memory and identity.